2017
DOI: 10.1016/j.ypmed.2016.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Preserving older adults' routine outdoor activities in contrasting neighborhood environments through a physical activity intervention

Abstract: While neighborhood design can potentially influence routine outdoor physical activities (PA), little is known concerning its effects on such activities among older adults attempting to increase their PA levels. We evaluated the effects of living in neighborhoods differing in compactness on changes in routine outdoor activities (e.g., walking, gardening, yard work) among older adults at increased mobility disability risk participating in the LIFE-Pilot PA trial (2003–07; ages 70–89 years; from Dallas, TX, San F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
(59 reference statements)
1
24
0
1
Order By: Relevance
“…These observations are consistent with those of previous studies in the general population [19, 21]; however, there is a contrast in some select findings in elderly people and those with chronic illnesses including hearing and vision impairments, and musculoskeletal diseases [15-17]. Our study showed that patients who live in more walkable areas exhibited significantly higher physical activity levels compared to those who live in less walkable areas, even though they were older, had a higher prevalence of CHF, and longer HD vintage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are consistent with those of previous studies in the general population [19, 21]; however, there is a contrast in some select findings in elderly people and those with chronic illnesses including hearing and vision impairments, and musculoskeletal diseases [15-17]. Our study showed that patients who live in more walkable areas exhibited significantly higher physical activity levels compared to those who live in less walkable areas, even though they were older, had a higher prevalence of CHF, and longer HD vintage.…”
Section: Discussionsupporting
confidence: 92%
“…Urbanicity of residence (i.e., urban, suburban, rural) as well as neighborhoods environment have been shown to be associated with physical activity levels in the general and HD populations [10-14]. Despite this, specific neighborhood characteristics have in some cases not been identified to be associated with physical activity levels in older adults and those with chronic illness [15-17]. …”
Section: Introductionmentioning
confidence: 99%
“…While several studies have evaluated the effect of ENDS minimum legal purchase age laws on traditional cigarette use (Friedman, 2015; Pesko et al, 2016; Pesko and Currie, 2016; Dave et al, 2017; Abouk and Adams, 2017), no published estimates exist on the effect of ENDS IVRs on cigarette use. In our current study, we estimate the impact of ENDS IVRs on adult pregnant women, rather than teenagers, to study this relationship unhindered by state efforts to restrict youth ENDS access through channels other than ENDS IVRs.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies have used difference-in-differences models to evaluate the effect of enacting these ENDS minimum legal sale age laws on use of tobacco among teens, with four of these studies suggesting that the laws raise teenage cigarette use (Friedman, 2015; Pesko et al, 2016; Pesko and Currie, 2016; Dave et al, 2017) and a fifth study suggesting that it does not and may even lower cigarette use for certain populations (Abouk and Adams, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…To date, only one previous study conducted in North America has explored the effects of objective neighborhood walkability on self-reported physical activity among older adults attempting to increase their physical activity levels [43]. Despite the lack of an objective measure of physical activity, King et al found no significant interactions for leisure walking between neighborhood walkability and study arm during a 12-month intervention program [43].…”
Section: Neighborhood Walkability and Physical Activitymentioning
confidence: 99%